"The Most Effective Experience was a Flexible and Creative Attitude"—Reflections on Those Aspects of Spiritual Care that were Lost, Gained, or Deemed Ineffective during the Pandemic. (April 2021) - Vandenhoeck, Anne; Holmes, Cheryl; Desjardins, Cate Michelle; Verhoef, Joost
This paper presents and discusses data from three of the qualitative questions in the international COVID-19 survey: What was the most important aspect of spiritual care that was lost during the pandemic? What was new to you during this pandemic? What are the new ways of delivering spiritual care you have experienced? Of these new experiences, what do you think was the most effective?